Enhancing Self-Confidence in English Speaking through Role-Play Activities - Ardhana, Bayu Adi; Sadikin, Irma Savitri (PROJECT (Professional Journal of English Education), 2025)
This study aimed to increase students' grade 9 student’s self-confidence in speaking English at one Junior High School in Jakarta. This study uses the Classroom Action Research (CAR) method which aims to solve the problem of students' lack of self-confidence in speaking English. This classroom action research uses the Kurt Lewin model. This study was conducted in 2 cycles where each cycle consists of planning, action, observation, and reflection stages. In obtaining data, the researcher used qualitative and quantitative methods. Qualitative data were obtained through observation, while quantitative data were obtained through tests (pre-test and post-test). The results of this study found that the use of the role-play method had been successful with the criteria that 75% of students achieved the target score ≥ 75 based on the Minimum Competency Criteria (KKM). The results obtained through the test showed that 80% of students had achieved the target minimum competency criteria score. In addition, the second criterion is that students become more active during the teaching and learning process, so the results of the observation show that by using the role-play method, students become more active and also confident in speaking English.